Pengembangan Model Buku Cerita Sejarah Pulau Cingkuak Untuk Meningkatkan Literasi Anak Usia Dini Di Tk Pembina 02 Painan - Yenti, Syahreni; Delfi Eliza (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Teachers have difficulty developing learning media that can provide stimulation to young children. This research aims to develop a storybook about the history of Cingkuak Island to improve literacy in early childhood. This type of research is development research using the ADDIE model. The subjects in this research were one learning content expert, one language expert, one history expert, and six teachers. The product trial subjects were 17 children. Observation, interviews, questionnaires, and documentation are used to collect data. The instrument used to collect data was a questionnaire sheet. The techniques used to analyze data are qualitative and quantitative descriptive analysis. The results of the research, namely the results of historical validation, obtained a score of 91.7% with a very valid category; the results of validation by historians obtained a score of 95.6% with very valid qualifications; the results of language validity obtained a score of 90.9% with a very valid category. The average teacher assessment is 95.2%, which is declared very practical. The assessment results given by the children were 97%, so the product was very practical. The effectiveness test results are 80%. It was concluded that children's storybooks introducing history in Persisisir Selatan Regency can increase literacy in Kindergarten in children aged 5-6 years.